Understanding history Book 3 grade 8 For grade 8 - Ismat Riaz (Karachi : Oxford university press, 2013)
"Understanding History 3" by Oxford University Press is a textbook designed for Grade 8 students, offering a comprehensive overview of significant historical events and themes. The book covers key periods in history, helping students to develop a deeper understanding of how past events have shaped the present. Through engaging narratives, primary sources, and critical thinking exercises, it encourages students to analyze and connect historical developments across different eras. The textbook aims to foster an appreciation of history while building essential skills in research, interpretation, and historical analysis.
Keywords: History-text book